Impact of Adventure-Based Approaches on the Self-Conceptions of Middle School Physical Education Students. (June 2018) - Gibbons, Sandra; Ebbeck, Vicki; Gruno, Jennifer; Battey, Glenda
Background: Research has identified enhancement of positive self-concept as an important outcome connected with participation in adventure-based activities in physical education (PE).Purpose: This study compared the effectiveness of Team Building Through Physical Challenges (TBPC) and Adventure Curriculum for Physical Education (ACPE) programs on the self-conceptions of middle school PE students. Both approaches include adventure-type tasks adapted for use in PE.Methodology/Approach: Participants consisted of 397 female ( n = 183) and male ( n = 214) students who were enrolled in Coeducational Grades 7 and 8 PE classes in three middle schools. Students in the treatment classes were exposed to either the TBPC condition or the ACPE condition during PE classes over 7 months, whereas students in the control group completed the regular PE curriculum that did not include activities from either approach.Findings/Conclusions: Results suggest that both approaches benefit the self-conceptions of children with each being particularly effective at changing those self-conceptions logically related to specific organizing themes. Specifically, ACPE was greater than TBPC, for global self-worth and perceived behavioral conduct. TBPC was greater than ACPE for perceived social approval.Implications: Incorporating either the TBPC or the ACPE program in middle school PE can benefit the self-conceptions of students.